EFEKTIVITAS LAYANAN KONSELING KELOMPOK MEDIA YOUTUBE VIDEO DENGAN TEKNIK MINDFULNESS THERAPY UNTUK MENGURANGI OVERTHINKING SISWA KELAS X SMA TUNAS KELAPA SAMARINDA - Ainun Nisa; Rury Muslifar; Dwi Sona; Muhaimin Abdillah (IKIP Siliwangi, 2026)
This study addresses the rising prevalence of overthinking among adolescents, which has been linked to decreased academic performance, emotional disturbances, and unhealthy social relationships. A quantitative approach was used with a true experimental design involving pre-test and post-test control groups. The participants consisted of six students selected through purposive sampling and divided into two groups: the experimental group received group counseling incorporating mindfulness therapy, while the control group received no intervention. The results revealed a significant reduction in overthinking levels in the experimental group, with the average pre-test score decreasing from 93 to 57.6 in the post-test. In contrast, the control group showed an insignificant change, from 92.3 to 90.6. The t-test analysis showed a significance value (2-tailed) of 0.001 < 0.05, indicating a statistically significant difference between the two groups. Furthermore, the N-Gain Score for the experimental group was 37.99%, categorized as moderate, whereas the control group scored only 1.78%, categorized as low or ineffective. These findings suggest that group counseling with mindfulness therapy is moderately effective in reducing overthinking in students